THE EFFECT OF USING CLOZE PASSAGE TECHNIQUE TOWARD STUDENTS READING COMPREHENTION ON NARRATIVE TEXT AT THE SECOND YEAR OF SMPN 1 RAMBAH HILIR - Yohana, Nina; Rahayu, Pipit; Sukma, Dian (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
This research was an experimental research, The purposes of this research were to find out studentsâreading comprehension on narrative text taught by using Cloze Passage Technique and taught withoutusing cloze Passage Technique at the second year students of SMPN1 Rambah Hilir. The researchfindings showed that the improvement from the score of t-test. The total score of t-test was 3.371.Based on t-table, 2.00 <3.371 > 2.65. Therefore, it could be concluded that there was a significanteffect of using Cloze Passage Technique toward students reading comprehension on narrative text atthe second year of SMPN 1 Rambah Hilir.